The Effect of Product Quality and Brand Image on Repurchase Intention of Honda Beat Motorcycles in Bandung City - Celvin Kardiman, Vincentius; Erpurini, Wala (International Journal of Management Science and Information Technology, 2026)
Due to intensifying competition within Indonesia’s automatic motorcycle sector, manufacturers are increasingly compelled to elevate product quality and solidify brand image to foster customer retention and drive repurchase intention. This study investigates the partial and simultaneous effects of product quality and brand image on the repurchase intention of Honda Beat owners in Bandung City. Employing a quantitative survey design, primary data were gathered from 120 purposively selected Honda Beat users. The dataset was subsequently evaluated using descriptive statistics, multiple linear regression, and hypothesis testing via IBM SPSS Statistics. The empirical findings reveal that both product quality and brand image exert a positive and statistically significant impact on repurchase intention individually. Concurrently, both factors significantly drive consumers’ intention to repurchase, demonstrating that superior product performance, reliability, durability, and a favorable brand perception strongly incentivize repeat purchases. Consequently, preserving high manufacturing standards while enhancing brand equity remains vital for cultivating customer loyalty and maintaining market competitiveness. Ultimately, this research adds to the marketing literature on automotive consumer behavior in urban Indonesia and offers strategic insights for manufacturers seeking to optimize customer retention.